Effects of Capital Flexion Exercise on Craniovertebral Angle, Trunk Control, Balance, and Gait in Stroke Patients with Forward Head Posture: A Randomized Controlled Trial - Dong-A Hyeon; Jeong-Seon Kim; Hyoung-Won Lim (Medicina)
Background and Objectives: Forward head posture (FHP) is associated with reduced stability limits, impaired balance performance, and compromised cervical proprioception. This study investigated the effects of capital flexion exercise (CFE) on the craniovertebral angle (CVA), trunk control, balance, and gait in chronic stroke patients with forward head posture. Materials and Methods: Twenty-six subjects were randomly assigned to the CFE group or the control group (n = 13 each). The CFE group underwent a familiarization process and performed CFE for 9 min per session, 3 times a week for 6 weeks, as well as the existing neurodevelopmental treatment (NDT). The control group received only the existing NDT. Results: The CVA, the Korean version of the Postural Assessment Scale for Stroke (K-PASS), the Berg Balance Scale (BBS), and the Timed Up and Go test (TUG) improved after the intervention in the CFE group (p < 0.05). In the control group, CVA and TUG improved after the intervention (p < 0.05). The CVA (d = 1.34, p = 0.002), K-PASS (d = 1.36, p = 0.000), and BBS (d = 1.68, p = 0.000) values of the CFE group showed statistically significant improvement compared to the control group. Although TUG improved in the CFE group, the between-group difference was not statistically significant (d = −0.28, p = 0.467). Conclusions: This study suggests that capital flexion exercises effectively improve craniovertebral angle, trunk control, and balance in chronic stroke patients with forward head posture.